Analisa Perencanaan Perlengkapan Persediaan Bahan Baku Produk Rotor Metode Material Requirement Planning (Studi Kasus: PT. Voith Paper Karawang) - Satrya Septiwijaya; Sukanta Sukanta (Jurnal Serambi Engineering, 2023)
Material Requirements Planning (MRP) is a system of planning and scheduling material requirements for production that requires several process stages or phases. This method is used for needs that are interdependent and reduce savings costs. The purpose of this research is to determine whether the Material Requirement Planning (MRP) method can be used to calculate the amount of raw material in rotor products, anticipating empty inventory, reducing overstock and minimizing expenses that must be incurred at PT. Karawang Voith paper. This study employs descriptive methods for data collection, including interviews and observation. The results show that the net need for raw material inventory is Rp. 203,918 and the quantity results in inventory ordering planning is Rp. 343,800. After taking into account planning plans from time to time in the future during the horizon of the Material Production Schedule, which takes into account the inventory status the result is Rp. 177,518